Chloride ion-doped polyaniline/carbon nanotube nanocomposite materials as new cathodes for chloride ion battery. (20th April 2018) - Zhao, Zhigang; Yu, Tingting; Miao, Yingchun; Zhao, Xiangyu
Abstract: Finding and optimizing the appropriate cathode materials in the electrolyte are critical to the development of chloride ion batteries. Herein, chloride ion-doped polyaniline/carbon nanotubes (PANI/CNTs) composite materials, which were prepared by an in situ chemical oxidative polymerization method using FeCl3 ·6H2 O as the oxidant, have been developed as new cathodes for chloride ion battery. The PANI/CNTs cathode showed reversible electrochemical energy storage through redox reactions of nitrogen species and chloride ion transfer, as confirmed by the results of the electrochemical testing and X-ray photoelectron spectroscopy. The structural configuration of PANI by the incorporation of conductive CNT carrier contributed to significant improvement in the electrochemical properties. More than 80 mAh g −1 stable capacity and a high Coulombic efficiency of about 99% were delivered. This work offers a promising strategy for designing chloride ion storage electrode and novel electrochemical systems. Highlights: Chloride ion-doped polyaniline material is firstly developed as new cathode for chloride ion battery. Reversible redox reactions of nitrogen species and Cl − transfer in polyaniline are proved. More than 80 mAh g −1 capacity and a high Coulombic efficiency of 99% are delivered.